The Effects of Time Pressure and Knowledge on Key Word Selection Behavior in Tax Research. - Spilker, Brian C. (The Accounting Review, 1995)
Abstract Focuses on the impact of time pressure and knowledge on tax researchers' ability to locate relevant authority. Declarative and procedural knowledge's enhancement of tax researchers' ability to select relevant key words; Interaction between time pressure and knowledge.